Human pathogenic virus-associated pseudolymphomas and lymphomas with primary cutaneous manifestation in humans and animals. - Wagner, M; Rose, V A; Linder, Roland; Schulze, H J; Krueger, G R (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 1998)
The etiologic role of viruses in cutaneous lymphoproliferative disorders is still controversial. In benign cutaneous pseudolymphomas of the human skin, human T-cell leukemia/lymphoma virus (HTLV) type I (HTLV-I), varicella zoster virus, Epstein-Barr virus (EBV), and human herpesvirus (HHV) 6 (HHV-6) are the viruses most often identified, whereas in malignant lymphoproliferation human immunodeficiency virus type 1 (HIV-1), HTLV-I/II, and EBV are more common. Coinfections with more than one virus species have occurred in a number of cases. HHV-8 in association with a lymphoproliferative lesion appears to be indicative of a malignant cutaneous lymphoma rather than of pseudolymphoma. Negative results are of no diagnostic value because of the relatively low number of virus-positive cases: a considerable proportion of studies (with a large number of subjects) have documented virus-negative findings. Perhaps with the exception of HIV-1, findings of viral infections seem to indicate secondary rather than primary infections. Reports on animal models associated with human pathogenic viruses are scarce.
Keywords: Animals; Herpesviridae; Herpesviridae Infections; Humans; Lymphoma, B-Cell; Lymphoma, T-Cell, Cutaneous; Pseudolymphoma; RNA Virus Infections; RNA Viruses; Skin Diseases; Skin Neoplasms; Virus Diseases